Genetics Analysis and Heritability of Fruit Characters in Muskmelon (Cucumis melo L.) Using Extreme Parental Differences - Sakulphrom, Sunisa; Chankaew, Sompong; Sanitchon, Jirawat (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Taeng-Thai is the Thai name for oriental pickling melon or muskmelon (Cucumis melo L.) which is a Cucumis species. Based on consumption as Thai traditional dessert, fruit characters at ripening stage are very important to improve the muskmelon cultivar. Understanding the genetic control of fruit traits is the key to a successful for crop improvement. Research aimed to determine the genetic effects, number of genes and heritability of fruit characters in muskmelon. The results have shown that both additive and dominant effects governed for fruit weight, fruit length, fruit width and fruit thickness with the number of gene as 40.26, 1.55, 10.70 and 11.10 genes, respectively. Simple phenotypic correlation coefficients shown, had a significant positive correlation among the four fruit traits. Due to the quantitative inheritance of fruit characters, quantitative traits loci (QTL) mapping of those traits were necessary to identify all controlling genes of fruit traits in further muskmelon improvement.